2017
DOI: 10.7441/joc.2017.02.03
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Micro-credit Programmes Focusing on Household Income, Expenditure and Savings: Evidence From Bangladesh

Abstract: This paper assesses the effectiveness of microfinance on household income, expenditure and savings. The survey examined those borrowers who had successfully completed at least three cycles of a loan. A household level survey (N=3000) was carried out to collect information about individuals receiving microcredit from one of the largest NGOs, ASA. The authors employed a multiple regression and discovered that the microcredit programme of ASA has a significant positive impact on household income, expenditures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…The study found that microcredit programs had a significant positive impact on household income, expenditure and savings. In addition, this study revealed that the level of education plays an important and significant role in increasing household income, expenditure and savings (Choudhury et al, 2017). Another study from Pakistan concluded that microfinance institutions have been superior in poverty alleviation and empowerment than conventional financial system approaches (Khan, Shaorong, & Ullah, 2017).…”
Section: The Purpose Of the Researchmentioning
confidence: 78%
See 2 more Smart Citations
“…The study found that microcredit programs had a significant positive impact on household income, expenditure and savings. In addition, this study revealed that the level of education plays an important and significant role in increasing household income, expenditure and savings (Choudhury et al, 2017). Another study from Pakistan concluded that microfinance institutions have been superior in poverty alleviation and empowerment than conventional financial system approaches (Khan, Shaorong, & Ullah, 2017).…”
Section: The Purpose Of the Researchmentioning
confidence: 78%
“…The efficacy of microfinancial institution in poverty alleviation han been noticeable in several developing countries, such as Bangladesh, even though the concept is still in debate (Afonso et al, 2011). In the same vein, Choudhury et al (2017) prove that microfinancial program has a positive effect on poverty alleviation and the increase of village household competitiveness in Bangladesh, with the result of increased living standard. Another research (Brief, 2015) in Bosnia and Herzegovina find that the efficacy of microfinance is only noticeable in small groups, while in Portugal (Afonso et al, 2011), the estimate of the failure rate of microfinance program was 20.6 percent in 2006-2009.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to the financial support provided by the Slovak government and other institutions such as the Microloan Program run by the Slovakian Business Agency, new microcredit or microfinance institutions, microenterprise development programs, non-profit financial intermediary organizations, microlending projects and programs, saving and credit cooperatives, intermediary programs, microenterprise zones, and microenterprise assistance programs can be set up or encouraged by government to ease access conditions and increase credit volumes. For instance, microfinance institutions do not ask for collateral that needs to be shown by borrowers to get credit (Ariful, Das, & Rahman, 2017). These institutions encourage microenterprises that urgently need credits and provide a wide range of credit options for microenterprises to ease credit access conditions (Atmadja et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In [35], it is stated that firms that use loans in the initial year of their activity are significantly more likely to survive and achieve a higher level of income three years after the establishment of the firm. Therefore, in [36], we considered the long-term consequences of lending to enterprises, namely, we studied the presence of a certain lag between the moment of taking a loan and the moment of receiving returns from it. It is worth mentioning the results of a study conducted in [37], which found a significant positive impact of microfinances on household income, spending, and savings.…”
Section: Microcredit Efficiency and Their Role In Ensuring Sustainable Developmentmentioning
confidence: 99%